Realities in the sexuality of the cuban elderly - Rodríguez Cabrera, Aida Leonor; Álvarez-Vázquez, Luisa; Sanabria-Ramos, Giselda (Horizonte Sanitario, 2015)
Objective : To identify references on the main sexuality characteristics of people aged 60 or over .Method: An analysis of the contents of published articles was carried out in Cuban and foreign scientifi publications from the year 2000 and onward. Information was obtained from Yearbooks, International Conference Reports and works considered as classical in the subject.Results : Population ageing and sexuality are not properly considered by health systems. There are only a few references that explore sexuality in the elderly and his aspirations, feelings, and ways of thinking on his healthcare and, more specifially, sexuality needs. Intimacy within an elderly couple is generally disregarded from the social and family points of view.Conclusions : The assessment of sexual activity in the elderly lacks a multidisciplinary approach since most of the predominating criteria are permeated by cultural inflences, taboos, myths and habits that negatively inflence it. Evidence points out to the existence of sexual activity and dysfunctions among the elderly, which indicates the need for a healthcare staf that has is properly trained for approaching anyissue related to this activity of life. The determining role of the health sector in this fild as coordinator of all the sectors and actors related to human sexuality and the ageing process, is not fully appreciated
Keywords: Sexuality; elderly; sexual and reproductive health